Anticancer Effects of 15d-Prostaglandin-J2 in Wild-Type and Doxorubicin-Resistant Ovarian Cancer Cells: Novel Actions on SIRT1 and HDAC - de Jong, Edwin; Winkel, Peter; Poelstra, Klaas; Prakash, Jai (PLOS ONE, 2011)
15-deoxy-delta-12,14-prostaglandin-J2 (15d-PGJ2), an arachidonic metabolite and a natural PPARγ agonist, is known to induce apoptosis in tumor cells. In this study, we investigated new therapeutic potentials of 15d-PGJ2 by determining its anticancer effects in wild-type and doxorubicin-resistant ovarian carcinoma cells. Despite high expression of resistance-inducing genes like MDR1, Bcl2 and Bcl-xl, 15d-PGJ2 strongly induced apoptosis in doxorubicin-resistant (A2780/AD) cells similar to the wild-type (A2780). This was found to be related to caspase-3/7- and NF-κB pathways but not to its PPARγ agonistic activity. 15d-PGJ2 also was able to reduce the doxorubicin resistance of A2780/AD cells at low doses as confirmed by the inhibition of gene expression of MDR1 (p-glycoprotein) and SIRT1 (a drug senescence gene). We also investigated effects of 15d-PGJ2 on cell migration and transformation using a wound-healing assay and morphological analyses, respectively. We found that 15d-PGJ2 inhibited migration most likely due to NF-κB inhibition and induced transformation of the round-shape A2780/AD cells into elongated epithelial cells due to HDAC1 inhibition. Using a 15d-PGJ2 analog, we found the mechanism of action of these new activities of 15d-PGJ2 on SIRT1 and HDAC1 gene expressions and enzyme activities. In conclusion, the present study demonstrates that 15d-PGJ2 has a high therapeutic potential to kill drug-resistant tumor cells and, the newly described inhibitory effects of this cyclo-oxygenase product on SIRT1 and HDAC will provide new opportunities for cancer therapeutics.